2017
DOI: 10.1039/c7mt00240h
|View full text |Cite
|
Sign up to set email alerts
|

Zinc’ing it out: zinc homeostasis mechanisms and their impact on the pathogenesis of human pathogen group A streptococcus

Abstract: Group A Streptococccus (GAS) is a major human pathogen that causes significant morbidity and mortality. Zinc is an essential trace element required for GAS growth, however, zinc can be toxic at excess concentration. The bacterial strategies to maintain zinc sufficiency without incurring zinc toxicity plays a crucial role in host-GAS interactions and has significant impact on GAS pathogenesis. Host deploys nutritional immune mechanisms to retard GAS growth by causing either zinc deprivation or zinc poisoning. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 80 publications
0
39
0
Order By: Relevance
“…4). S. uberis contains the ATP-binding cassette (ABC) permease AdcABC, a conserved zinc acquisition system among streptococci (37). We observed that the zinc-specific solute binding protein (SBP), adcA (CGZ53_03345), was downregulated 4.5 log 2 -fold in response to PBT2zinc ( Fig.…”
Section: Resultsmentioning
confidence: 89%
“…4). S. uberis contains the ATP-binding cassette (ABC) permease AdcABC, a conserved zinc acquisition system among streptococci (37). We observed that the zinc-specific solute binding protein (SBP), adcA (CGZ53_03345), was downregulated 4.5 log 2 -fold in response to PBT2zinc ( Fig.…”
Section: Resultsmentioning
confidence: 89%
“…Zinc is an essential micronutrient for all organisms, serves as a structural or catalytic cofactor in 5 to 6% of proteins in the bacterial proteome (22)(23)(24), and can play an important role in the expression of key virulence factors (25)(26)(27)(28)(29)(30)(31)(32). However, high concentrations of zinc are toxic, possibly due to competition with other relevant metal ions (24,33), inhibition of key enzymes and essential metabolic reactions in the cell (32,34,35), and/or induction of membrane stress (36).…”
mentioning
confidence: 99%
“…2B,C), which are involved in many crucial biological processes and are essential for bacterial survival in the environment or in the infected host (28). In particular, zinc has recently been shown to be essential for pathogenic streptococci in their growth, morphology and virulence during infection (42, 43).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, several zinc transporters have been identified to contribute to zinc homeostasis and virulence in pathogenic streptococci (42, 43). In most streptococci, zinc acquisition involves a high-affinity zinc-ABC transporter, which is comprised of an integral membrane component (AdcB), an ATPase (AdcC) and one or several zinc-binding proteins (AdcA, AdcAII, Lbp, or Lmb) (42, 4446).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation